PENGARUH TQM TERHADAP KINERJA OPERASIONAL YANG DIMEDIASI OLEH ORGANSASI PEMBELAJARAN - Ichlas Nur Alam; Wahyuningsih Santosa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Operational performance is something that will determine the progress or decline of a company. If organizations perform poorly then what happens is a decline in the company. The purpose of this study was to determine the total quality management of operational performance mediated by a learning organization. This research is a type of verification research using the method of explanatory research where a research n that explains the clause relationship between research variables by testing the hypothesis. The results of this study show that based on the test results, it is known that TQM has a positive and significant effect on Operational Performance. This ability can be seen from the test results where the p values ​​score has sig. < 0.05. By implementing TQM practices, it can help increase customer satisfaction, employee satisfaction and productivity so that employees are more motivated in identifying ways to improve the delivery process and are able to reduce damage and ensure that company operations run more efficiently. This ability can be seen from the test results where the p values ​​score has sig. < 0.05. The existence of TQM will force good people to get better, and bad people are forced to be good.